Incentivized vehicle relocation in vehicle sharing systems. (December 2018) - Angelopoulos, Alexandros; Gavalas, Damianos; Konstantopoulos, Charalampos; Kypriadis, Damianos; Pantziou, Grammati
Highlights: The vehicle stock imbalance problem in one-way vehicle sharing systems is addressed. User-based vehicle relocations are used to avoid supply-and-demand mismatches. Dynamic allocations of vehicles to users are based on incentivization schemes. Price incentives reward users acting in favor of the system. Incentives are based on the priorities of vehicle relocations among stations. Abstract: The asymmetric demand-offer problem represents a major challenge for one-way vehicle sharing systems (VSS) affecting their economic viability as it necessitates the engagement of considerable human (and financial) resources in relocating vehicles to satisfy customer demand. In this paper, we propose a novel approach which involves user-based vehicle relocations to address supply-and-demand mismatches; in our approach, VSS users are offered price incentives so as to accept picking up their vehicle from an oversupplied station and/or to drop it off to an under-supplied station. The system incentivizes users based on the priorities of vehicle relocations among stations, taking into account the fluctuating demand for vehicles and parking places at different stations over time. A graph-theoretic approach is employed for modeling the problem of allocating vehicles to users in a way that maximizes the profit of the system taking into account the budget the VSS can afford to spend for rewarding users, as well as the users' strategic behavior. We present two different schemes for incentivizing users to act in favour of the system. Both schemes consider budget constraints and are truthful and budget-feasible. We have extensively evaluated our approach through simulations which demonstrated significant gain with respect to the number of completed trips and system revenue. We have also validated our approach through pilot trials conducted in a free-floating e-motorbike sharing system in the framework of an EU-funded research project.